2023
DOI: 10.1002/admt.202300389
|View full text |Cite
|
Sign up to set email alerts
|

A Porous Wrinkled Graphitic Carbon as Corrosion‐Resistant Carbon Support for Durable Fuel‐Cell Catalysts

Abstract: The lifespan of proton‐exchange membrane fuel cells heavily relies on the durability of the carbon support of cathode catalysts. However, commercial carbon supports like ketjenblack (KB) and Vulcan carbon (VC) face the challenge of balancing porosity, surface area, and electrochemical stability. To address this issue, a 3D porous wrinkled graphitic carbon (PWGC) is designed and synthesized using a catalyst‐free, plasma‐enhanced chemical vapor deposition approach. The resulting PWGC possesses a hierarchically p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…6e). 119 Pt nanoparticles were firmly attached to 3D porous graphitic carbon, preventing migration or aggregation with a stable electrochemical surface area (ECSA) after 10 000 stability cycling (Fig. 6f ).…”
Section: Carbon Support Modificationmentioning
confidence: 99%
“…6e). 119 Pt nanoparticles were firmly attached to 3D porous graphitic carbon, preventing migration or aggregation with a stable electrochemical surface area (ECSA) after 10 000 stability cycling (Fig. 6f ).…”
Section: Carbon Support Modificationmentioning
confidence: 99%
“…99 Introducing heteroatom dopants (e.g., N and Fe) can enhance the carbon oxidation resistance, resulting in the lower intensity of CO 2 ionic current. 181,182 Luka et al revealed that a higher content of sp 2 hybridization and a lower ratio of surface carboxyl can boost the corrosion resistance. 183 The reversible formation of a passive film during carbon corrosion is also evidenced in the DEMS study.…”
Section: Carbon Corrosionmentioning
confidence: 99%
“…10j and k). 179 Other compounds such as NiB, 62 metal hydroxide 91,181 and metal phosphides 106 were also effective in suppressing carbon corrosion through DEMS measurements. Additional strategies have been demonstrated by DEMS studies as well to be powerful in inhibiting carbon corrosion (Fig.…”
Section: Applicationsmentioning
confidence: 99%